Synthesis and Properties of a New Class of Fully Conjugated Azahexacene Analogues1. (5th May 2014) - Yue, Wan; Suraru, Sabin‐Lucian; Bialas, David; Müller, Matthias; Würthner, Frank
Abstract Acenes are a traditional class of polycyclic aromatic hydrocarbons (PAHs) which attracted considerable interest during the last decade because of their outstanding p‐channel semiconductor properties. More recently, N‐heteroacenes have been prepared. These molecules have been shown to be more stable and can exhibit n‐channel semiconductor properties. Inspired by these archetype PAHs, we synthesized a novel class of highly persistent azahexacene analogues 3 a–d. These molecules are composed of a core of four fused five‐membered rings derived from their respective diketopyrrolopyrroles. These new π‐conjugated scaffolds show broad and intense absorption in the visible region and possess low‐lying HOMO and LUMO levels, leading to much better stability compared to that of acenes and most heteroacenes.